(untitled) (Plant Bulletin, 2025)
Grewia asiatica locally known as Phalsa is an important fruit-bearing plant with diverse associated microbial communities that may influence plant health and physiological performance. Fungi are the eukaryotic microorganisms which are present almost in everywhere. The present study aimed to investigate the diversity of fungal microflora associated with different plant parts of G. asiatica. Fungal microflora were isolated from different parts of G. asiatica including stem, root, fruit, leaf and soil. Further, fungal characterization was carried out to confirm the fungal species. Aspergillus niger, Aspergillus fumigatus, Aspergillus flavus, Aspergillus terreus, Alternaria alternata, Fusarium oxysporum and Colletotrichum falcatum. Molecular identification was further performed using ITS sequencing and phylogenetic analysis which confirmed the evolutionary relationships of the isolated species with reference sequences. A total of eight fungal species belonging mainly to the phylum Ascomycota were isolated, with Aspergillus species showing predominance across most plant parts. Fungal diversity indices revealed higher diversity in soil and stem samples, while leaf samples exhibited the lowest diversity and similarity. Heat map analysis further supported variation in fungal diversity among plant compartments. The effect of the phyllosphere microbial community on photosynthetic pigments was assessed, revealing significantly higher photosynthetic pigment contents in plants treated with the phyllosphere microbial community compared to non-treated plants. Overall, the results indicate that fungal microflora associated with G. asiatica exhibit organ-specific distribution patterns and that the phyllosphere microbial community positively influences chlorophyll content and plant physiological performance